2016
DOI: 10.15405/epsbs.2016.11.02.17
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Halal Restaurant Patronage Intention: The Role of Perception, Culture and Religiosity

Abstract: Restaurants providing halal (permissible according to Islamic jurisprudence) food are important to Muslims. However, many factors influence customers' intention to patronise halal restaurants. This study examines the antecedents of patronage of halal restaurants. The study questions whether there is an effect of perceived value, perceived usefulness and culture on the intention to patronise halal restaurants and whether religiosity moderates the relationship among these variables. The purpose of this study is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Previous studies that related to consumer behaviour towards purchasing halal products found that religiosity was an antecedent of behavioural intention and proven to significantly, positively, and directly influenced behavioural intention (Alam, Janor, Zanariah, Wel, & Ahsan, 2012;Ahmad et al, 2015;Kusumawardhini, Hati, & Daryanti, 2016;Varinli, Erdem, & Avcilar, 2016). However, those findings were not supported by Fara, Hati, and Daryanti's (2016), their findings revealed that religiosity did not directly influence behavioural intention to patronize the halal restaurant. Therefore, religiosity role as the antecedent of behavioural intention in purchasing and consuming halal food cannot be generalized yet.…”
Section: Introductionmentioning
confidence: 81%
“…Previous studies that related to consumer behaviour towards purchasing halal products found that religiosity was an antecedent of behavioural intention and proven to significantly, positively, and directly influenced behavioural intention (Alam, Janor, Zanariah, Wel, & Ahsan, 2012;Ahmad et al, 2015;Kusumawardhini, Hati, & Daryanti, 2016;Varinli, Erdem, & Avcilar, 2016). However, those findings were not supported by Fara, Hati, and Daryanti's (2016), their findings revealed that religiosity did not directly influence behavioural intention to patronize the halal restaurant. Therefore, religiosity role as the antecedent of behavioural intention in purchasing and consuming halal food cannot be generalized yet.…”
Section: Introductionmentioning
confidence: 81%
“…Perception is essentially a cognitive process experienced by everyone in understanding information about their environment. both through sight, hearing, appreciation, feeling and smell (Fara et al, 2016;Naylor & Frank, 2000;Rafiki, 2019;Simbolon, 2008). Perception is also defined as a process that makes us aware of the many stimuli or stimuli that affect our senses.…”
Section: Perceptionmentioning
confidence: 99%
“…According to Rahimah Mohamed Yunos (2013) Overall, the success of the halal industry requires coordination and participation of various parties and strategic marketing strategies in addition to various other factors that contribute to placing "Halal" as one of the attributes consumers consider to buy products/services. Andreina Fara (2016) shows that halal certification in restaurants produces a better opinion of restaurants among consumers. In addition, halal certification is also seen as useful for consumers in determining consumer behavior.…”
Section: Theoretcal Basismentioning
confidence: 99%